Breath of oblivion - Broaddus, Maurice (New York : Tor Publishing Group, 2024)
"Maurice Broaddus's Breath of Oblivion is the second book in the Astra Black trilogy, where the futuristic technology of Black Panther meets the scale of The Expanse and the intricate political maneuverings of Game of Thrones. "Not to be missed."-Washington Post on Sweep of Stars Maurice Broaddus's returns with Breath of Oblivion, the second book in his Astra Black trilogy, that explores the struggles of an empire. Epic in scope and intimate in voice, it follows members of the Muungano empire-a far-reaching coalition of city-states that stretches from Earth to Titan - as it faces renewed threats to their progress."--
Keywords: Space colonies -- Fiction; Space warfare -- Fiction; Life on other planets -- Fiction; Imperialism -- Fiction; Science fiction; Novels